Generalized interstitial granuloma annulare - response to adalimumab - Werchau, Siegfried Arthur; Enk, Alexander; Hartmann, Martin (International journal of dermatology, 2010)
Background Cause and pathogenesis of granuloma annulare are poorly understood. A foreign-body granuloma formation induced by an unknown inciting antigen is suspected. Generalized forms often coincides with recalcitrant progression and frustrated experimental therapies. Methods We report a case of generalized interstitial granuloma annulare resolving completely after treatment with adalimumab. An initial dose of 80 mg was administered subcutaneously followed by a maintenance dose of 40 mg every two weeks. Results Already after two weeks, the eruptions became less infiltrated and paled. After a follow up of 7 weeks, only a residuum of postinflammatory hyperpigmented maculae without infiltration presented. The initially affected body surface area of over 35% reduced to less than 5%. Histopathological examination revealed a significant reduction in the interstitial histiocytic infiltration and the precipitations of mucin. Conclusion Although adalimumab should not be first line therapy for granuloma annulare, our case showed that it may profit well-selected patients and shorten disease duration.
Gesehen am 29.11.2023